2007
DOI: 10.1007/s10532-007-9100-3
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of phenol and 4-chlorophenol by the yeast Candida tropicalis

Abstract: Biodegradation of phenol and 4-chlorophenol (4-cp) using a pure culture of Candida tropicalis was studied. The results showed that C. tropicalis could degrade 2,000 mg l(-1) phenol alone and 350 mg l(-1) 4-cp alone within 66 and 55 h, respectively. The capacity of the strain to degrade phenol was obviously higher than that to degrade 4-cp. In the dual-substrate system, 4-cp intensely inhibited phenol biodegradation. Phenol beyond 800 mg l(-1) could not be degraded in the presence of 350 mg l(-1) 4-cp. Comparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 34 publications
3
28
0
1
Order By: Relevance
“…The maximum tolerable phenol concentration that Candida tropicalis H can degrade efficiently was 2000 mg/l. These findings are in good agreement with those found by Jiang et al (2007b), where Candida tropicalis was able to degrade up to 2000 mg/l of phenol. The toxicity threshold concentration of phenol against microbial strains is different from a strain to another.…”
Section: Nutritional and Environmental Factors Affecting Growth And Psupporting
confidence: 92%
“…The maximum tolerable phenol concentration that Candida tropicalis H can degrade efficiently was 2000 mg/l. These findings are in good agreement with those found by Jiang et al (2007b), where Candida tropicalis was able to degrade up to 2000 mg/l of phenol. The toxicity threshold concentration of phenol against microbial strains is different from a strain to another.…”
Section: Nutritional and Environmental Factors Affecting Growth And Psupporting
confidence: 92%
“…It showed that the model regression agreed well with the experimental data. The values of kinetic parameters of mutant strain CTM 2 were bigger than those of its parent strain (12), which indicated that mutant strain CTM2 possessed a higher potential to degrade phenol.…”
Section: ϫ2mentioning
confidence: 94%
“…Fialová et al (9) reported that the yeast Candida maltosa can degrade phenol at concentrations up to 1,700 mg liter Ϫ1 . A wild strain was isolated from acclimated activated sludge in our lab with the potential to degrade 2,000 mg liter Ϫ1 phenol within 66 h (12). To further promote phenol biodegradation potential, improvement of microorganisms is of great importance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The universal toxicity and ubiquitous nature of phenol make its biodegradation a topic of great interest (ATSDR, 2006). Although the earliest studies of phenol biodegradation focused on bacteria, there have been a growing number of fungi studied for their ability to degrade phenol, including members of the genera Trichosporon, Cryptococcus, Rhodotorula, Rhodococcus, Aspergillus, Penicillium, Cladosporium, Trichoderma, Phanerochaete, Candida and Fusarium (Harris and Ricketts, 1962;Dagley, 1967;Neujahr and Varga, 1970;Gaal and Neujahr, 1979;Rubin and Schmidt, 1985;Alexievaa et al, 2004;Atagana, 2004;Santos and Linardi, 2004;Bergauer et al, 2005;Margesin et al, 2005;Krallish et al, 2006;Singh, 2006;Stoilova et al, 2006;Jiang et al, 2007). Fungi are often able to thrive under environmentally stressed conditions (low nutrient availability, low moisture, low pH and low temperature) and unlike bacteria, they can extend their biomass through environmental matrices through hyphal growth, making their potential for metabolism of organic pollutants particularly promising (Buchan et al, 2003;Atagana, 2004;Margesin et al, 2005;de Boer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%